Exploring Neuro-Linguistic Programming (NLP) to Support EFL Students in Thesis Proposal Writing - Daulay, Irma Khoirot; Suci, Dewi Nur; Al Azis, Edwin Nuvianto; Perrodin, David D.; Makasara, Hanis Ribut (Journal of Languages and Language Teaching, 2025)
The aim of the current research was to explore how the lecturer uses neurolinguistic programming (NPL) to maximize the students' potential when creating thesis proposals. This study poses two research questions: 1) What challenges do students have when writing their thesis proposals? and 2) How may NLP communication help students write their thesis proposals. A case study design that was employed in this study. Open-ended questionnaire was distributed to the students of English education department. The results of this study firstly highlight that the students’ difficulties in writing involved their lack of knowledge, psychological aspect and both of them. ability in writing skills, understanding contents, motivation. Another finding showed that the NLP communication in the form of teachers’ affirmations can bring the positive influence on the student’s perspectives and attitudes to write their proposal.  This study concludes that teachers can establish a more encouraging and productive learning environment by using ideas from positive psychology and neuro-linguistic programming (NLP).